Sociological Analysis of Social Assistance Fund Allocation in the 2024 General Election: Democracy and Popular Sovereignty - Mulyadi, Dedi; Amalia, Mia; Mulyana, Aji (Journal La Sociale, 2024)
The Executive General Election and Legislative General Election in 2024 is a democratic process to elect the President and Vice President as the head of the executive and People's Representatives (DPR, DPD, Provincial DPRD, Regency and City) directly by citizens in Indonesia both domestically and abroad. In general, general elections are an important mechanism in a modern democratic system that allows people to participate in determining state leaders and policies. The policy of allocating Grants and Social Assistance funds during the 2024 Election, precisely at the campaign stage, can potentially be part of Money Politic/money politics. This scientific writing is carried out using a normative juridical system with the aim of this research to investigate and provide an in-depth understanding of the Sociological Background of the Allocation of Social Assistance Funds during the Presidential and Legial Elections, the Allocation Policy of Social Assistance Funds that have the potential for Political Corruption in the Presidential and Legislative Elections, and the social impact and political impact of the Allocation of Social Assistance Funds during the political campaign period of the Presidential and Legislative Elections. Where this scientific writing is expected to be an alternative thought on the various problems above, in the implementation of the next General Election and the allocation of proportional and non-excessive Grants and Social Assistance policies.